Detecting Rates, Trends and Determinants of Cesarean Section Deliveries in Iran Using Generalized Additive Mixed Models (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The present study aimed to investigate the trend of cesarean section and its related factors through the recent years.Methods: The study data containing delivery information from Hamadan hospitals and are recorded from 2001 to 2014. The data were analyzed through the generalized additive mixed models using R software (v. 3.2.2).Results: cesarean rate in this study was about 42%. According to the results, the trend of cesarean deliveries almost increased in the recent years. A significant relationship was found between the average age and elective cesarean rate, but, the pregnancy rate didn’t have a significant effect on the elective cesarean rate.Conclusion: Cesarean section rate was more than the allowed limit by world health organization (WHO) that is 15%. Although cesarean delivery is preferred to natural vaginal delivery in the case the mother’s or infant’s life is in danger, it should not replace natural delivery for any reason. Natural vaginal delivery can be promoted by providing the society with the knowledge about the advantages of natural delivery and complications of cesarean section.